Access and allocation in earth system governance: lessons learnt in the context of the Sustainable Development Goals - Joyeeta Gupta (2020)
© 2020, The Author(s). Researching socio-ecological justice issues in earth system governance can be operationalized through an Access (securing minimum needs) and Allocation (allocating the remaining resources, responsibilities and risks) framework. This paper synthesizes the review articles in this special issue. It concludes that (a) although international trade, investment and aid aim to enhance access, efficiently allocate resources and reduce risk, in practice the volume of trade and investment, the geographical distance between production and consumption, the pursuit of competitiveness and use of market instruments have concentrated wealth at great cost to socio-ecological justice; (b) research on food, water, energy, climate change and biodiversity reveal multiple linkages among the sustainable development goals, underlining the limitations of sectoral and incremental approaches to socio-ecological justice, for example, for smallholders; (c) while access issues are becoming difficult for politicians to ignore, allocation issues are being side-stepped because they draw too much attention to the underlying causes of inequality and poverty, (d) corrective justice is not enough, substantive justice approaches are needed emphasizing a rights-based framework and allocation cannot be exclusively left to market forces and mechanisms when it concerns public and merit goods; and (e) the terms access and allocation, although individually used, are not popular as a paired framework in the socio-ecological justice literature, but remain highly salient and cover the key justice issues for improving earth system governance.